Love + work : how to find what you love, love what you do, and do it for the rest of your life - Buckingham, Marcus (Boston, MA : Harvard Business Review Press, 2022)
"We're in the middle of an epidemic of stress and anxiety. A global pandemic has wreaked havoc on our lives. Average life expectancy in the United States is down. At work, less than 16 percent of us are fully engaged. In many high-stress jobs, such as distribution centers, emergency room nursing, and teaching, incidences of PTSD are higher than for soldiers returning from war zones. We're getting something terribly wrong. We've designed the love out of our workplaces, and our schools too, so that they fail utterly to provide for or capitalize on one of our most basic human needs: our need for love. As Marcus Buckingham shows in this eye-opening, uplifting book, love is an energy, and like all forms of energy, it must flow. It demands expression-and that expression is "work." Whether in our professional accomplishments, our relationships, or our response to all the many slings and arrows of life, we know that none of this work will be our best unless it is made with love. There's no learning without love, no innovation, no service, no sustainable growth. Love and work are inextricable. Buckingham first starkly highlights the contours of our loveless work lives and explains how we got here. Next, he relates how we all develop best in response to other human beings. What does a great work relationship look like when the other person is cued to your loves? What does a great team look like when each member is primed to be a mirror, an amplifier, of the loves of another? Finally, he shows how you can weave love back into the world of work as a force for good, how you can use your daily life routines to pinpoint your specific loves, and how you can make this a discipline for the rest of your life. Today, too often, love comes last at work, and we are living the painful consequences of this. Love + Work powerfully shows why love must come first-and how we can make this happen"--
Introductions -- Part one: Signs of love. Where did the love go? ; Your wyrd ; Love is attention ; Instinct ; Flow ; It just clicks ; Love lives in the details -- Part two: Seven devils. Group-think ; Excellence curse ; Mis-instinct ; Feedbacking ; Fear-fighting ; Rate-me-rank-me ; Suckitup --- Part three: Make love + work come alive. I see you, I love you ; Scavenger hunt for love ; Love @ work ; Love in learning ; Your children are not your children -- Epilogue: Over to you.
Includes bibliographical references (pages 289-290) and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
WorldCat record variable field(s) change: 050
Keywords: Employee motivation; Job satisfaction; Love; Work -- Psychological aspects; Job Satisfaction; Love; Personnel -- Motivation; Satisfaction au travail; Amour; Travail -- Aspect psychologique; Employee motivation; Job satisfaction; Love; Work -- Psychological aspects; elektronické knihy; electronic books